Hybrid immunity and protection against infection during the Omicron wave in Malta. Issue 1 (31st December 2023) - Cauchi, John Paul; Dziugyte, Ausra; Borg, Maria-Louise; Melillo, Tanya; Zahra, Graziella; Barbara, Christopher; Souness, Jorgen; Agius, Steve; Calleja, Neville; Gauci, Charmaine; Vassallo, Pauline; Baruch, Joaquin
ABSTRACT: By December 2021, administration of the third dose of COVID-19 vaccinations coincided with the spread of the Omicron variant in Europe. Questions had been raised on protection against infection conferred by previous vaccination and/or infection. Our study population included 252, 433 participants from the COVID-19 vaccination registry in Malta. Data were then matched with the national testing database. We collected vaccination status, vaccine brand, vaccination date, infection history, and age. Using logistic regression, we examined different combinations of vaccine dose, prior infection status and time, and the odds of infection during the period when the Omicron variant was the dominant variant in Malta. Participants infected with Sars-Cov-2 prior to the Omicron wave had a significantly lower odds of being infected with the Omicron variant. Additionally, the more recent the infection and the more recent the vaccination, the lower the odds of infection. Receiving a third dose within 20 weeks of the start of the Omicron wave in Malta offered similar odds of infection as receiving a second dose within the same period. Time since vaccination was a strong determinant against infection, as was previous infection status and the number of doses taken. This finding reinforces the importance of future booster dose provision especially to vulnerable populations.